Studies on diesel engine exhaust gas for retrieving the waste heat through Triple Tube Heat Exchanger (TTHE) through different tubes. Issue 2 (15th June 2022) - Raman, Mohan; Saravanan, Perumal; Muthusamy, Suresh; Subramaniam, Shankar
ABSTRACT: This paper presents a methodology to recover the waste heat from the diesel engine exhaust gas via triple tube heat exchanger (TTHE) with various intermediate tubes like corrugated tube, helically finned tube, dimpled tube, protrusion tube, and then compared with double tube heat exchanger numerically and experimentally. Due to its practical catastrophic nature by application, only limited work has been done in TTHEs. In many studies, the dimpled tube is used for only fluid flows and not used for gaseous states due to boundary layer problems. In TTHE, the intermediate tube carries exhaust gases of diesel engine, while the inside and outside of the tube carries water, respectively, where the Reynolds number ( Re ) varyies from 4, 000 to 11, 000. The rate of heat transfer and fluid flow attributes of TTHE for counter flow and parallel flow orders with different mass flow rates are investigated. The temperature variations of plain tube and different intermediate tubes are analyzed with computational fluid dynamics (CFD) and also experimentally. The outer pipe's outer diameter is 101 mm, intermediate pipe's outer diameter is 76 mm, and inner pipe's outer diameter is 50 mm and the thickness of each of the three tubes is 1.5 mm with length of 2, 000 mm singly. The TTHE thermal performances and fluid flow characteristics are expressed by the Nusselt number ( Nu ), Effectiveness (e), and overall heat transfer coefficient (U). The results obtained numerically by CFD and the experimental value of TTHE were compared with the double tube heat exchanger. The counter flow kind of TTHE with dimpled tube geometry produces the best results. The greatest waste heat recovered using dimpled tube TTHE is roughly 6.279 kW at full load circumstances, according to the findings.